Nutritive value of sugarcane treated with sodium hydroxide and added of ground corn ears - Andrade, João Batista de; Júnior, Evaldo Ferrari; Braun, Gilberto (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to determine the nutritive value of sugarcane treated with 1,0% of sodium hydroxide plus 0, 40, 80 and 120 kg of ground corn ears/ton of chopped sugarcane. The experiment was carried out at Instituto de Zootecnia, in Nova Odessa, SP, Brazil, in a randomized complete block design, with four replications. Intake and digestibility trials were conducted in 10, 10 and 5 day periods, corresponding respectively to adaptation, intake and feces collection of female sheep. Dry matter intake and dry matter digestibility increased linearly with the addition of ground corn ears. Total digestible nutrients was not altered with the addition of ground corn ears.